2001
DOI: 10.1139/g01-104
|View full text |Cite
|
Sign up to set email alerts
|

Synaptonemal complex analysis in spermatocytes and oocytes of turbot, Scophthalmus maximus (Pisces, Scophthalmidae)

Abstract: A surface-spreading synaptonemal complex (SC) technique was used to analyze spermatocytes and oocytes of turbot (Scophthalmus maximus) to visualize the process of chromosome synapsis. The total SC length was 205 +/- 12 microm in males and 172 +/- 29 microm in the only female analyzed. A representative SC karyotype of turbot was obtained. Each SC showed lateral elements of equal length. No bivalent exhibiting atypical synaptic behaviour that could be associated with heteromorphic sex chromosomes was observed, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
14
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 3 publications
5
14
0
Order By: Relevance
“…This global estimate is similar to the sex-averaged values reported for other fish species using the same method, as in Dicentrarchus labrax (Chistiakov et al 2005). However, the turbot represents one of the smallest genomes among cultured fish (Wang et al 2007), with estimates of haploid C-values ranging from $0.65 pg (Cuñado et al 2001) to 0.86 pg (Hardie and Hebert 2004). The estimated genome size in turbot (,800 Mb) would render 530 kbp/cM on average, although the relationship between physical and genetic distance may vary among regions of the turbot genome and between sexes (as seen below).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This global estimate is similar to the sex-averaged values reported for other fish species using the same method, as in Dicentrarchus labrax (Chistiakov et al 2005). However, the turbot represents one of the smallest genomes among cultured fish (Wang et al 2007), with estimates of haploid C-values ranging from $0.65 pg (Cuñado et al 2001) to 0.86 pg (Hardie and Hebert 2004). The estimated genome size in turbot (,800 Mb) would render 530 kbp/cM on average, although the relationship between physical and genetic distance may vary among regions of the turbot genome and between sexes (as seen below).…”
Section: Discussionsupporting
confidence: 82%
“…Recently, the development of genetic markers in turbot has greatly increased, particularly regarding microsatellites (Pardo et al 2006(Pardo et al , 2007. Compared to other vertebrate and many fish species, the turbot genome is small (Cuñado et al 2001;Hardei and Hubert 2004), about four times smaller than the human genome, and one of the smallest genomes among farmed fish (Wang et al 2007). At present, the knowledge of turbot genome organization is limited to the well-established mitotic and meiotic karyotypes (Bouza et al 1994;Cuñado et al 2001Cuñado et al , 2002Pardo et al 2001), which revealed an n ¼ 22 haploid chromosome number and no sex-linked chromosome heteromorphisms.…”
Section: T He Turbot (Scophthalmus Maximus; Scophthalmidae;mentioning
confidence: 99%
“…Sex-associated heteromorphisms previously had not been detected either in mitotic or in the .11-fold longer meiotic chromosomes of turbot (Bouza et al 1994;Cuñado et al 2001). As in most fish species (Almeida-Toledo and Foresti 2001), this observation shows the primitive evolutionary condition of sex chromosomes in this species.…”
Section: Discussionsupporting
confidence: 63%
“…Although some differences between families can be observed in the production process at farms, sex ratio is usually balanced at $1:1. Neither mitotic nor meiotic chromosomes have shown sex-associated heteromorphisms in turbot (Bouza et al 1994;Cuñado et al 2001). The proportion of sexes observed in triploid and especially gynogenetic progenies moved Cal et al (2006a,b) to suggest an XX/XY mechanism in turbot with some additional, either environmental or genetic, factor involved.…”
mentioning
confidence: 96%
“…In addition, there has been significant progress in the past decade toward elucidation of the regulatory mechanisms of gametogenesis and maturation using fish as experimental models [20,21,22]. The structure of the SC in several fishes has been reported [23,24,25,26], but its molecular components have not yet been identified in any fish. To study the SC in fish, we selected the medaka fish Oryzias latipes as an experimental system for the following reasons [27,28,29]: 1) Under artificial reproductive conditions, medaka undergoes continuous spermatogenesis and oogenesis, providing experimental materials all year round, 2) medaka spermatogenesis can be reproduced in a cell culture system [30,31,32] In this study, we cloned medaka homologs of Sycp1 and Sycp3, MeSycp1 and MeSycp3 (for medaka Sycp1 and Sycp3, respectively).…”
mentioning
confidence: 99%